Mesenchymal Stem Cells Regulate the Innate and Adaptive Immune Responses Dampening Arthritis Progression - R. A. Contreras; F. E. Figueroa; F. Djouad; P. Luz-Crawford (Stem Cells International)
Mesenchymal stem cells (MSCs) are multipotent stem cells that are able to immunomodulate cells from both the innate and the adaptive immune systems promoting an anti-inflammatory environment. During the last decade, MSCs have been intensively studied in vitro and in vivo in experimental animal model of autoimmune and inflammatory disorders. Based on these studies, MSCs are currently widely used for the treatment of autoimmune diseases such as rheumatoid arthritis (RA) characterized by complex deregulation of the immune systems. However, the therapeutic properties of MSCs in arthritis are still controverted. These controversies might be due to the diversity of MSC sources and isolation protocols used, the time, the route and dose of MSC administration, the variety of the mechanisms involved in the MSCs suppressive effects, and the complexity of arthritis pathogenesis. In this review, we discuss the role of the interactions between MSCs and the different immune cells associated with arthritis pathogenesis and the possible means described in the literature that could enhance MSCs therapeutic potential counteracting arthritis development and progression.